Queue Analysis System For Improving Efficiency Of Service - Josep Indra; Haryadi Sarjono (Universitas Airlangga, 2010)
This research aim to know how much most effective car queue done by PT. KAM, in Jakarta, a company moving to gives car repair service (car workshop) which during the time provide 6 kinds of service facility (M), whether with facility and employer addition will result maximal advantage. method of Research used is descriptive method with research Type of Case Study, while its Variable is probability no unit / people in system (Po), the total customer staying in queue system (Ls), mean of customer time await in queue system (Ws), total mean of customer stay in queue (Lq), and mean time of customer await in queue (Wq). Result of this research is adding one kind of server without officer of company may get advantage equal to Rp. 10.136.000 compared to add one server and one officer. Advantage obtained is equal to Rp. 8.936.000.